Testing of Field Grading Materials For HVDC Cable Joints - Kappadan, Sajil (My University, 2025)
Abstract HVDC cable systems are designed to transmit large amounts of electricity over long distances with minimal losses. Most failures in these systems happen because of issues with cable accessories like joints and terminations. They are caused by strong electric fields appearing in such components due to geometrical features of the designs and inhomogeneities in the structure of the insulation system incorporating various materials. To enhance the performance of cable accessories, electric field control in the insulation is crucial. To address this, so-called field grading materials (FGMs) can be used to even out the electric field distributions. Thanks to their non-linear properties, these materials secure normal operations of the cable system and also are capable of handling events like lightning overvoltage and switching impulses. This thesis focuses on exploring electrical and mechanical properties of FGMs by testing samples of materials with different types and concentration of fillers at various temperatures and electric field strength. The focus is on a comparative analysis, where the properties of EPDM (Ethylene Propylene Diene Monomer) are taken as a reference. New materials with good electrical and mechanical properties are selected based on specific criteria, followed by measurements of their non-linear conductivity. Experimental results show that three selected materials met the criteria for nonlinear conductivity. To further evaluate their performance as a base for building a large scale component, electrothermal simulations of a 525 kV DC cable joint made of those materials have been conducted for different voltage levels including nominal, type test and lightning impulse voltages. The simulation results show minimal differences in the field grading effects caused by the selected FGMs applied in different locations of the cable joint, likely because of similar non-linear behavior of their properties in the studied ranges of temperatures and electric stresses.